Mineral chemistry of augen gneisses from Tamakoshi–Likhu Khola area in east Nepal - Regmi, Kamal Raj (Journal of Nepal Geological Society, 2007)
In the Tamakoshi–Likhu Khola area of east Nepal, augen gneisses are found in three different tectonic units, i.e. in the Higher Himalayan (HH) crystalline zone, in the footwall of the Main Central Thrust (MCT), and in the core of the Lesser Himalayan (LH) dome. Selected minerals, particularly K-feldspar (Kfs), plagioclase (Pl), garnet (Grt), biotite (Bt), muscovite (Ms), and tourmaline (Tur) were analysed from the gneisses. The Pl from the HH gneisses contains the highest concentration of anorthite component in comparison with the Pl from the gneisses of the MCT footwall and the LH dome. The Mg# of Bt from the gneisses of the HH crystalline zone, MCT footwall, and LH dome varies from 0.35 to 0.5, 0.24 to 0.49, and 0.14 to 0.23, respectively. The Bt compositions of augen gneisses from all three zones plot in the field of Bt of peraluminous (including S-type) granite. The compositions of Ms from the MCT footwall plot in the field of secondary Ms of granitic rocks, while those of Ms from the gneisses of the LH dome plot in the field of primary Ms on the Miller’s diagram. The Grt from the HH gneisses shows a retrograde zoning pattern, but that from the MCT footwall shows a prograde growth zoning pattern. Journal of Nepal Geological Society, 2006, Vol. 33 p.11-22